187k views
2 votes
Solve it in algebraically
y= 4x – 11
y=-8x + 13

1 Answer

1 vote

Answer:

y=4x−11

Step 1: Flip the equation.

4x−11=y

Step 2: Add 11 to both sides.

4x−11+11=y+11

4x=y+11

Step 3: Divide both sides by 4.


(4x)/(4) =
(y+11)/(4)

x=
(1)/(4) y +
(11)/(4)

y=-8x + 13

Step 1: Flip the equation.

−8x+13=y

Step 2: Add -13 to both sides.

−8x+13+−13=y+−13

−8x=y−13

Step 3: Divide both sides by -8.


(-8x)/(8) =
(y- 13)/(-8)

x=
(-1)/(8)y +
(13)/(8)

User Dave Mansfield
by
4.7k points